The impact of impaired mitochondrial function on retrograde signalling: a meta-analysis of transcriptomic responses. - Schwarzländer, M; König, A; Sweetlove, L; Finkemeier, I (2012)
Mitochondria occupy a central position in cellular metabolism. Their protein complement must therefore be dynamically adjusted to the metabolic demands of the cell. As >95% of mitochondrial proteins are encoded by nuclear DNA, regulation of the mitochondrial proteome requires signals that sense the status of the organelle and communicate it back to the nucleus. This is referred to as retrograde signalling. Mitochondria are tightly integrated into the network of cellular processes, and the output of mitochondrial retrograde signalling therefore not only feeds back to the mitochondrion, but also regulates functions across the cell. A number of transcriptomic studies have assessed the role of retrograde signalling in plants. However, single studies of a specific mitochondrial dysfunction may also measure secondary effects in addition to the specific transcriptomic output of mitochondrial signals. To gain an improved understanding of the output and role of mitochondrial retrograde signalling, a meta-analysis of 11 transcriptomic data sets from different models of plant mitochondrial dysfunction was performed. Comparing microarray data from stable mutants and short-term chemical treatments revealed unique features and commonalities in the responses that are under mitochondrial retrograde control. In particular, a common regulation of transcripts of the following functional categories was observed: plant-pathogen interactions, protein biosynthesis, and light reactions of photosynthesis. The possibility of a novel mode of interorganellar signalling, in which the mitochondrion influences processes in the plastid and other parts of the cell, is discussed.